What might the 'art of critique' in humanities and social sciences academic writing look like? - Henderson, Juliet (Teaching in higher education, 2023)
This paper conceptualises and explores 'the art of critique' in student writing in the humanities and social sciences [Foucault 1997. "What is Critique?" In: The Politics of Truth. English Translation. Translated from French by Lysa Hocroth & Catherine Porter. In Dits et Ecrits for original French. Los Angeles: Semiotexte. Accessed July 10, 2015. http://anthropos-lab.net/wp/wp-content/uploads/2011/12/Foucault-Critique.pdf]. Its starting principle is that education lacks vigour without an understanding of how to play with and disrupt the rules of Western reason, as well as respect them: a practice of playing and interrupting the same to generate something new that is beyond 'use-value' [Derrida 2006. Specters of Marx. New York: Routledge Classics, 201] yet can also be used to signify 'use-value'. Fundamental to this idea is the question of the 'agency' of the subject in orders of discourse, oscillating between consent and resistance. To conceptualise the dynamics of interrupting the historical traditions of academic writing more closely, Foucault's notion of 'care of the self' and Derrida's field of analysis, deconstruction, are interrogated. A few examples of such dynamics in student work are then tentatively presented as heuristics for catalysing the 'art of critique' in writing.